Internalisation for Strengthening Professionalism and Resilience of Employees at SMI: A Qualitative Study in Pekalongan - Arif Budiharjo (Cahaya Abadi Publisher, 2026)
This study examines strategies to strengthen professionalism and mental resilience among savings and financing marketing officers at three Sharia Microfinance Institutions (SMIs) in Pekalongan City and its surrounding areas. Employing a qualitative research design, data were collected through in-depth interviews, field observations, and analysis of internal institutional documents. The data were subsequently analyzed using triangulation techniques, pattern matching, and systematic visualization of findings to ensure credibility and analytical rigor. The findings reveal that high work intensity, performance targets, and competitive field conditions significantly contribute to burnout risk, work stress, and psychological discomfort among employees. However, value-based interventions emphasizing the internalization of Islamic work ethics and structured mental development programs were found to enhance motivation, professional commitment, work ethic, and employee engagement. These results underscore the strategic importance of cultivating professional character and psychological resilience as sustainable organizational efforts to improve employee performance. The study contributes to the development of human resource management practices in Islamic microfinance institutions, particularly in responding to competitive pressures while maintaining ethical and professional standards.